2016
DOI: 10.1103/physrevd.94.034007
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of perturbative QCD at a 100 TeV future hadron collider

Abstract: Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modied, adapted, performed, displayed, published, or sold in whole or part, without prior written permission from the American Physical Society.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 215 publications
(295 reference statements)
0
15
0
Order By: Relevance
“…The contribution I 1 contains the conditions on x 1 , x 2 , θ 1 , θ 2 such that k 1 sets the mass (ρ = ρ 1 ) and has the higher transverse momentum, κ 1 > κ 2 . It also contains the condition for the Y-splitter cut 7 If we keep into account finite y corrections, we should actually use fcut = y/(1 + y), which is what we have done in practice in our Monte Carlo simulations. 8 Since we explained the approximations we have made in the previous section we shall no longer explicitly specify that the NLO corrections here are computed in the limit of soft and collinear emissions.…”
Section: Y-splitter With Trimming: Fixed-order Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution I 1 contains the conditions on x 1 , x 2 , θ 1 , θ 2 such that k 1 sets the mass (ρ = ρ 1 ) and has the higher transverse momentum, κ 1 > κ 2 . It also contains the condition for the Y-splitter cut 7 If we keep into account finite y corrections, we should actually use fcut = y/(1 + y), which is what we have done in practice in our Monte Carlo simulations. 8 Since we explained the approximations we have made in the previous section we shall no longer explicitly specify that the NLO corrections here are computed in the limit of soft and collinear emissions.…”
Section: Y-splitter With Trimming: Fixed-order Resultsmentioning
confidence: 99%
“…7 We firstly note that, at leading order, for a soft emission to pass Y-splitter it must have an energy fraction x > y. When one applies trimming afterwards such an emission is unaffected as, with our choice of f cut trimming removes only emissions with x < y.…”
Section: Y-splitter With Trimming: Fixed-order Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, an analysis of dimension-six gluon operators in multijet production at a Future Circular Hadron Collider (FCC) with √ s = 100 TeV. Further details on this study can be found in [62,182]. Second, a study on an anomalous triple gauge coupling in Z-boson pair production at the LHC, based on the corresponding CMS measurement [183].…”
Section: Physics Beyond the Standard Modelmentioning
confidence: 99%
“…[105] (see also Refs. [106][107][108][109][110][111] for related theoretical work). Since the detector layout of a 100 TeV machine is likely to change towards an improved electromagnetic calorimeter coverage [112,113], this mapping from ðZ → e þ e − Þ þ jet and γ þ jet could also be performed without relying on an extrapolation into the jet-acceptance region beyond the lepton and photon acceptance regions jηj < 2.5 that is imposed by the current LHC setup.…”
Section: A 14 and 100 Tev Hadron Collidersmentioning
confidence: 99%